PERANAN IBNU MUJAHID DALAM TERBENTUKNYA QIR?’AT SAB’AH: Kajian Kitab As-Sab’ah Fi Al-Qir?’ah - Zuhrupatul Jannah (UIN Mataram, 2019)
This paper discusses about the role of Ibn Mujahid and how hiseffortto format of the qir?‘ah sab'ah. Understanding, or at least knowing qir?'ah is an urgent matter, not only because qir?'ah is a scientific discipline of its own, but also because this science allows people who understand it to be able to explain some related scholarship, such as fiqh, law and interpretation itself. Based on this then the concepts of qir?‘ah sab'ah, qir?‘ah ‘asyr, and arba’ah‘ asyr emerge. Among the concepts above, which are widely known by the public are qir?‘ah sab’ah, seven variations of reading (al-Qir?‘ah al-Sab’ah). What a great attention of Ibn Mujahid to the science of qir?'at has led him to compose books that make it easy for the prosecutors to study different kinds of qir?'at in the Qur'an. The book what is meantion is al-Sab'ah fî al-Qir?’ah.